Herbal Formula SS-1 Increases Tear Secretion for Sjögren’s Syndrome - Chang, Ching-Mao; Wu, Po-Chang; Lin, Jr-Rung; Jan Wu, Yeong-Jian; Luo, Shue-Fen; Hsue, Yin-Tzu; Lan, Joung-Liang; Pan, Tai-Long; Wu, Yu-Ting; Yu, Kuang-Hui; Wei, Yau-Huei; Chang, Hen-Hong (Frontiers in Pharmacology, 2021)
Background: Sjögren’s syndrome (SS) is an autoimmune inflammatory disease that primarily affects the exocrine glands, leading to glandular dysfunction. The hallmark symptoms of SS are dry eyes and mouth, compromising the quality of life of patients and decreasing their capacity to perform their daily activities. Objective: This study aims to evaluate the efficacy of the herbal formula SS-1 for its potential therapeutic benefits for patients with Sjögren’s syndrome. Materials and methods: The bioactivity profile of SS-1 was determined using four different SS-1 concentrations across 12 human primary cell systems of the BioMAP profile. After that, a randomized, double-blind, crossover, placebo-controlled trial were performed including 57 patients treated with SS-1 for 28 weeks. Results: Biologically multiplexed activity profiling in cell-based models indicated that SS-1 exerted anti-proliferative activity in B cells and promoted anti-inflammatory and immunomodulatory activity. In clinical trial, the treatment of SS-1 revealed a significant improvement in both eyes by Schirmer’s test, which were increased by 3.42 mm (95% CI, 2.44–4.41 mm) and 3.45 mm (95% CI, 2.32–4.59 mm), respectively, and a significant reduction in artificial tear use, which was −1.38 times/day, 95% CI, −1.95 to −0.81 times/day,. Moreover, these results indicated that the increases in BAFF and BCMA levels were dampened by 53.20% (295.29 versus 555.02 pg/mL) and 58.33% (99.16 versus 169.99 pg/mL), respectively. Conclusion: SS-1 treatment significantly inhibited B-cell maturation antigen. No serious drug-related adverse effects were observed. Oral SS-1 administration may be a complementary treatment for Sjögren’s syndrome. Trial registration: Clinicaltrials.gov: NCT02110446. Registered April 10, 2014, https://clinicaltrials.gov/ct2/show/record/NCT02110446